Comparison of a Direct Drive Wind Turbine with and without LSS-Coupling Regarding Air Gap Displacement. Issue 5 (September 2020) - Baseer, A; He, Y; Schelenz, R; Kari, A; Roscher, B; Jacobs, G
Abstract: Wind turbines (WT) are highly coupled and complex systems. The dynamic interaction between various components is especially pronounced for multi megawatt wind tur-bines. As a result, the design process is generally split into several phases. [3] The first step consists of creating a global aero-elastic model that includes essential dynamics of structural components using the minimum possible number of degrees of freedom (DOFs), with the most important simplifications concerning the drivetrain and rotor nacelle assembly. This approach is not suitable to analyse the generator air gap of a direct drive wind turbine. In this paper a more detailed simulation model is depicted, which calculates realistic deformation of the wind turbine and in particular the displacement between the generator-rotor and generator-stator. For these analysis a detailed multibody simulation (MBS) model of a generic direct drive WT is set up and used to analyse the generator air gap [3]. Several concepts of a direct drive WT are available on the market. One of them includes a coupling between the hub and generator-rotor to decouple the input wind loads from the generator and thus to decrease the impact on the generator air gap deflection [5]. The aim of this paper is to compare such a concept with a conventional concept without coupling.